Socio-demographic, clinical and treatment characteristics of relapsing schizophrenic patients. (February 2013) - San, Luis; Bernardo, Miquel; Gómez, Agustín; Martínez, Pedro; González, Beatriz; Peña, Mario
Abstract Aims: To define the clinical profile of relapsing patients with schizophrenia attended in daily practice. Method: Patients with schizophrenia/schizoaffective disorder admitted to short-stay/acute-care psychiatric units were eligible provided that data for the previous 3 years and for the next 12 months after discharge were collected. Results: Remarking features in 1646 patients (68% men) included low family support (34%), primary education (48%), schizophrenia as the main diagnosis (77%), duration of illness > 10 years (60%), mean number of previous hospitalizations of 2.74, non-adherence as the main reason of hospitalization (58.6%), treatment with a mean of two different antipsychotics and differences in adherence according to antipsychotic medication (P < 0.0001) (highest rates for depot atypical antipsychotics). The relapse rate was 38.6%. There were no differences in the number of relapsing patients according to antipsychotic drugs. Discussion and conclusion: The profile of relapsing schizophrenic patients may be defined as a male subject, aged 30–45 years, with primary education level, more than 10 years of disease' duration, low family support, moderately and severely ill, treated with multiple antipsychotic drugs, and poor to moderate adherence. Differences in relapse according to antipsychotic types were not observed but long-acting second generation antipsychotic drugs showed the highest percentage of maximum adherence.